NorthStar. - Haugnes, Natasha 1965-; Maher, Beth 1965- (Longman, 2004)
With NorthStar, Second Edition (Series Editors: Frances Boyd and Carol Numrich), students explore fascinating content while building language competence and critical thinking skills. The best-selling NorthStar series, now in its Second Edition, offers two strands: a reading and writing strand and a listening and speaking strand. Both strands stimulate students' imagination, encourage critical thinking, and promote personal expression.